2013
DOI: 10.3758/s13415-012-0148-0
|View full text |Cite
|
Sign up to set email alerts
|

A connectionist model of category learning by individuals with high-functioning autism spectrum disorder

Abstract: Individuals with autism spectrum disorder (ASD) show atypical patterns of learning and generalization. We explored the possible impacts of autism-related neural abnormalities on perceptual category learning using a neural network model of visual cortical processing. When applied to experiments in which children or adults were trained to classify complex two-dimensional images, the model can account for atypical patterns of perceptual generalization. This is only possible, however, when individual differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 92 publications
5
45
0
1
Order By: Relevance
“…As previously shown (Dovgopoly & Mercado, 2013), A Type 1 children showed generalization patterns similar to those previously found for TD children after training with distorted prototypes (Church et al, 2010). However, they showed relatively poorer generalization after training with the PrototypeOnly task (Fig.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…As previously shown (Dovgopoly & Mercado, 2013), A Type 1 children showed generalization patterns similar to those previously found for TD children after training with distorted prototypes (Church et al, 2010). However, they showed relatively poorer generalization after training with the PrototypeOnly task (Fig.…”
Section: Resultssupporting
confidence: 66%
“…Previous research showed that this percentage of endorsements of random shapes predicts the distinctive A Type 1 and A Type 2 generalization patterns seen in children with HFASD (Dovgopoly & Mercado, 2013). Also, the TD children in our previous research (Church et al, 2010) meet this A Type 1 criterion.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations